2010
DOI: 10.1242/dev.045807
|View full text |Cite
|
Sign up to set email alerts
|

Bazooka is required for polarisation of the Drosophila anterior-posterior axis

Abstract: SUMMARYThe Drosophila anterior-posterior (AP) axis is determined by the polarisation of the stage 9 oocyte and the subsequent localisation of bicoid and oskar mRNAs to opposite poles of the cell. Oocyte polarity has been proposed to depend on the same PAR proteins that generate AP polarity in C. elegans, with a complex of Bazooka (Baz; Par-3), Par-6 and aPKC marking the anterior and lateral cortex, and Par-1 defining the posterior. The function of the Baz complex in oocyte polarity has remained unclear, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(128 citation statements)
references
References 68 publications
(93 reference statements)
7
119
1
1
Order By: Relevance
“…Furthermore, in par1 and baz/par3 mutants, osk mRNA is delocalized to a central focus (Shulman et al 2000;Tomancak et al 2000;Becalska and Gavis 2010;Doerflinger et al 2010). In some mutant alleles of these genes, bcd mRNA is relatively unaffected (Shulman et al 2000), whereas in others, bcd mRNA localizes along the lateral cortex in a similar manner to Egl depletion (Becalska and Gavis 2010;Doerflinger et al 2010).…”
Section: Egl and Oocyte Microtubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in par1 and baz/par3 mutants, osk mRNA is delocalized to a central focus (Shulman et al 2000;Tomancak et al 2000;Becalska and Gavis 2010;Doerflinger et al 2010). In some mutant alleles of these genes, bcd mRNA is relatively unaffected (Shulman et al 2000), whereas in others, bcd mRNA localizes along the lateral cortex in a similar manner to Egl depletion (Becalska and Gavis 2010;Doerflinger et al 2010).…”
Section: Egl and Oocyte Microtubulesmentioning
confidence: 99%
“…In some mutant alleles of these genes, bcd mRNA is relatively unaffected (Shulman et al 2000), whereas in others, bcd mRNA localizes along the lateral cortex in a similar manner to Egl depletion (Becalska and Gavis 2010;Doerflinger et al 2010). In some mutant alleles of baz, the oocyte nucleus is retained at the posterior (Becalska and Gavis 2010;Doerflinger et al 2010), whereas in some mutants of par-1, migration of the oocyte nucleus is unaffected (Shulman et al 2000).…”
Section: Egl and Oocyte Microtubulesmentioning
confidence: 99%
“…Recent studies have shown that Lgl is involved in the polarization of the A-P axis in the Drosophila oocyte (Doerflinger et al, 2010;Fichelson et al, 2010;Li et al, 2008;Tian and Deng, 2008). In the early oocyte, Lgl is required for the proper posterior translocation of cell fate determinants as well as the centrosomes (Fichelson et al, 2010;Tian and Deng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dlg, Scrib and Lgl are also important in follicular epithelium morphogenesis and subsequent polarization of the Drosophila oocyte, albeit in a different way as in other epithelia. The work of several groups has shown that Lgl is an essential regulator of posterior follicle cells and that phosphorylation of Lgl together with Par-1 and Par-3 is required for the posterior translocation of oocyte-specific proteins and germline determinants (Fichelson et al 2010, Doerflinger et al 2010. Mutation of the aPKC phosphorylation site in Par-1 results in the uniform cortical localization of Par-1 and the loss of cortical microtubules (Doerflinger et al 2010).…”
mentioning
confidence: 99%
“…The work of several groups has shown that Lgl is an essential regulator of posterior follicle cells and that phosphorylation of Lgl together with Par-1 and Par-3 is required for the posterior translocation of oocyte-specific proteins and germline determinants (Fichelson et al 2010, Doerflinger et al 2010. Mutation of the aPKC phosphorylation site in Par-1 results in the uniform cortical localization of Par-1 and the loss of cortical microtubules (Doerflinger et al 2010). Dlg and Scrib are required differentially for patterning in both the anterior and posterior follicular epithelium (Li et al 2009) and genetically interact with Lgl for posterior follicle cell induction , suggesting a common regulatory pathway in this process.…”
mentioning
confidence: 99%